Limited validity of Mayo endoscopic subscore in ulcerative colitis with concomitant primary sclerosing cholangitis - Wohl, Pavel; Krausova, Alzbeta; Wohl, Petr; Fabian, Ondrej; Bajer, Lukas; Brezina, Jan; Drastich, Pavel; Hlavaty, Mojmir; Novotna, Petra; Kahle, Michal; Spicak, Julius; Gregor, Martin (World journal of gastrointestinal endoscopy, 2024)
BACKGROUND: Ulcerative colitis (UC) with concomitant primary sclerosing cholangitis (PSC) represents a distinct disease entity (PSC-UC). Mayo endoscopic subscore (MES) is a standard tool for assessing disease activity in UC but its relevance in PSC-UC remains unclear. AIM: To assess the accuracy of MES in UC and PSC-UC patients, we performed histological scoring using Nancy histological index (NHI). METHODS: MES was assessed in 30 PSC-UC and 29 UC adult patients during endoscopy. NHI and inflammation were evaluated in biopsies from the cecum, rectum, and terminal ileum. In addition, perinuclear anti-neutrophil cytoplasmic antibodies, fecal calprotectin, body mass index, and other relevant clinical characteristics were collected. RESULTS: The median MES and NHI were similar for UC patients (MES grade 2 and NHI grade 2 in the rectum) but were different for PSC-UC patients (MES grade 0 and NHI grade 2 in the cecum). There was a correlation between MES and NHI for UC patients (Spearman's r = 0.40, P = 0.029) but not for PSC-UC patients. Histopathological examination revealed persistent microscopic inflammation in 88% of PSC-UC patients with MES grade 0 (46% of all PSC-UC patients). Moreover, MES overestimated the severity of active inflammation in an additional 11% of PSC-UC patients. CONCLUSION: MES insufficiently identifies microscopic inflammation in PSC-UC. This indicates that histological evaluation should become a routine procedure of the diagnostic and grading system in both PSC-UC and PSC.